2021
DOI: 10.1111/rode.12847
|View full text |Cite
|
Sign up to set email alerts
|

Contract farming, community effect, and farmer valuation of biofortified crop varieties in China: The case of high‐zinc wheat

Abstract: Biofortification is a feasible and cost‐efficient approach to reduce human micronutrient deficiency, but few studies have investigated its economic value from the perspective of producers. We propose an actual output‐based payment card (AOPC) method to elicit producer valuation of biofortified high‐zinc wheat in North China Plain and assess the impacts of contract farming and community network on their valuation. Unlike financial payments, AOPC uses actual output as the payment vehicle. The results show that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Interestingly, the relationship between landholding size and crop adoption is more nuanced. While six studies found no significant association (Abebe et al, 2013;Li et al, 2021), this aspect is marked with complexities.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, the relationship between landholding size and crop adoption is more nuanced. While six studies found no significant association (Abebe et al, 2013;Li et al, 2021), this aspect is marked with complexities.…”
Section: Discussionmentioning
confidence: 91%
“…This model assumes that households are the primary decision-makers in agricultural production and that they allocate their resources among activities to maximize their utility. Adekambi et al (2020b); Li et al (2021); Mwiti et al (2020); and Smale et al (2016) relied on the Lancasterian demand theory, which posits that consumers derive utility from the characteristics or properties of a good rather than the good being the direct object of utility. It is noteworthy that 11 studies in the articles did not refer to any theoretical model underpinning their research.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations